Transforming narratives into educational tools: the collaborative development of a transformative learning tool based on Nicaraguan adolescents' creative writing about intimate partner violence. (March 2019) - Singleton, Robyn; Picado Araúz, María de la Paz; Trocin, Kathleen; Winskell, Kate
The use of narrative has become increasingly popular in the public health, community development, and education fields. Via emotionally engaging plotlines with authentic, captivating characters, stories provide an opportunity for participants to be carried away imaginatively into the characters' world while connecting the story with their own lived experiences. Stories have been highlighted as valuable tools in transformative learning. However, little published literature exists demonstrating applications of stories in group-based transformative learning curricula. This paper describes the creation of a narrative-based transformative learning tool based on an analysis of Nicaraguan adolescents' meaning-making around intimate partner violence (IPV) in their creative narratives. In collaboration with a Nicaraguan organization, US researchers analyzed a sample of narratives ( n = 55; 16 male-authored, 39 female-authored) on IPV submitted to a 2014 scriptwriting competition by adolescents aged 15–19. The data were particularly timely in that they responded to a new law protecting victims of gender-based violence, Law 779, and contradicted social-conservative claims that the Law 779 destroys family unity. We incorporated results from this analysis into the creation of the transformative learning tool, separated into thematic sections. The tool's sections (which comprise one story and three corresponding activities) aim to facilitate critical reflection, interpersonal dialogue, and self- and collective efficacy for social action around the following themes derived from the analysis: IPV and social support; IPV and romantic love; masculinity; warning signs of IPV; and sexual abuse. As a collaboration between a public health research team based at a US university and a Nicaraguan community-based organization, it demonstrates the potential in the age of increasingly smooth electronic communication for novel community–university partnerships to facilitate the development of narrative-based tools to support transformative learning.